Antimicrobial-resistant E. coli and Enterococcus spp. Recovered from urban community gardens. (February 2020) - Perera, Liyanage Nirasha; Mafiz, Abdullah Ibn; Amarasekara, Nirosha Ruwani; Chang, Eric; Krishnoji Rao, Vidhya Bai; Zhang, Yifan
Abstract: This study analyzed Escherichia coli ( E. coli ) and Enterococcus spp. from vegetables and soil in three urban community gardens in metro Detroit, Michigan. Bacteria were identified by PCR and 16S rRNA sequencing, followed by antimicrobial susceptibility testing, pulsed-field gel electrophoresis (PFGE), and whole-genome sequencing (WGS). E. coli was isolated from 11 of 19 (57.9%) soil samples and 23 of 48 (48%) vegetables, whereas Enterococcus spp. from 17 of 19 (89.5%) soils and 38 of 48 (79%) vegetables. The most common Enterococcus species identified in soil were Ent. mundtii (29.4%), Ent. casseliflavus (11.8%), Ent. durans (11.8%), and Ent. faecalis (11.8%). In contrast, Ent. faecalis (81.6%) was most abundant in vegetables. Disk diffusion revealed that 18 of 34 E. coli (52.9%) and 45 of 55 Enterococcus spp. (81.8%) were resistant to at least one antimicrobial agent. Ampicillin resistance was the only resistance phenotype observed in E. coli . Streptomycin resistance prevailed in Enterococcus spp. and was demonstrated by 11 of 17 (64.7%) isolates in soil and 30 of 38 (78.9%) from vegetables. WGS on selected isolates based on antimicrobial susceptibility profiles showed the predominance of multidrug efflux pumps in E. coli regardless of their susceptibility phenotypes. Enterococcus spp. carried resistance genes to aminoglycoside, macrolides-lincosamides-streptogramin (MLS), and tetracycline. Prophage and Tn 916 were identified in E. coli and Enterococcus spp., respectively. The data revealed diverse E. coli and Enterococcus spp. associated with urban food production environment. The occurrence of antimicrobial resistance phenotypes and resistance genes in vegetables indicates potential food safety concern due to the ready-to-eat nature of most vegetables. Highlights: Diverse E. coli and Enterococcus spp. are prevalent in vegetables and soil in urban community gardens. Antimicrobial resistance phenotypes and resistance genes occur in E. coli and Enterococcus spp. in soil and vegetables. Multidrug efflux pump genes and mobile genetic elements (MGE) are common in the isolates.